2020
DOI: 10.3390/cancers12082054
|View full text |Cite
|
Sign up to set email alerts
|

PARP Inhibitor Resistance Mechanisms and Implications for Post-Progression Combination Therapies

Abstract: The use of PARP inhibitors (PARPi) is growing widely as FDA approvals have shifted its use from the recurrence setting to the frontline setting. In parallel, the population developing PARPi resistance is increasing. Here we review the role of PARP, DNA damage repair, and synthetic lethality. We discuss mechanisms of resistance to PARP inhibition and how this informs on novel combinations to re-sensitize cancer cells to PARPi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 177 publications
0
61
0
6
Order By: Relevance
“…The best approach would be to implement treatment that would prevent the appearance of drug-resistant clones. There is a number of ongoing trials evaluating the efficacy of combinations of PARPi with other drugs[ 34 , 54 ]. Several studies demonstrated the potentially curative impact of high-dose chemotherapy for BRCA1/2 mutation carriers; however, the use of this treatment is associated with excessive adverse effects[ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The best approach would be to implement treatment that would prevent the appearance of drug-resistant clones. There is a number of ongoing trials evaluating the efficacy of combinations of PARPi with other drugs[ 34 , 54 ]. Several studies demonstrated the potentially curative impact of high-dose chemotherapy for BRCA1/2 mutation carriers; however, the use of this treatment is associated with excessive adverse effects[ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been proposed such as alterations in PARP1 leading to increase in PARP1 catalytic activity or removal of PARP trapping, restoration of HRR via BRCA reversion mutations or demethylation of BRCA promoter as reviewed by Lee and Matulonis. [137] It is anticipated that the number of patients that are resistant to PARPis will continue to rise and thus it is critical to understand the mechanisms of PARPi resistance for optimizing treatment strategies such as targeted combination therapy. [137] In summary, several PARPis have been approved as therapeutic and maintenance therapy for multiple cancer types, typically based on the presence of germline or somatic BRCA PVs.…”
Section: Therapeutic Implications For Icismentioning
confidence: 99%
“…Resistance to PARP inhibitors is an active area of research and reviewed in detail elsewhere [47][48][49]. Briefly, the main proposed mechanisms of resistance to PARP inhibitors include restoration of homologous recombination activity (e.g., by reactivation of BR-CAm through secondary mutations), altered PARP expression, increased efflux of PARP inhibitors from cells, and stabilization of stalled replication forks (thereby reducing doublestrand breaks).…”
Section: Implications For Clinical Practicementioning
confidence: 99%